KAJIAN IMPLEMENTASI PROGRAM REVITALISASI KAWASAN KOTA LAMA SEBAGAI KAWASAN PARIWISATA DI KOTA SEMARANG - Galang Adit Hutsa Dewantara; Fitriyah .; Puji Astuti (Journal of Politic and Government Studies, 2017)
The old town area of semarang city often gets the spotlight as one of assets of the inheritance. The old town which is in fact very experienced strategic shift functions, resulting in the death of the area. The efforts made by the Government in Semarang is Program of revitalization as a form of reviving the area, buildings, roads and environment to boost economic activity, social, tourism and culture. The program is part of revitalization strategy and tourism development programme implemented by the Government of the Semarang city. Revitalizing the old town area of semarang is a manifestation of support fully agains preserving tourism and culture while simultaneously empowering potential of Semarang as one of tourism so as to provide a more significant contribution in organizing, development and empowerment of Goverment assets Semarang. This research is a policy studies to analyze how the implementation of the program of revitalizing the old town area as a Tourism area in Semarang City and know the obstacles and factors by using a descriptive qualitative research methods. Descriptive research can be defined as a study that attempted to describe a phenomenon or events systematically. With the techniques of data collection through interviews, documents and observations. The research results obtained stated that in general the success of implementation of policy the old town area Revitalization Program is currently quite good but yet everything is still in the process of developing optimal towards Old Town area as a tourism destination in 2020. There are still some obtacles in doing stages Revitalization due to the implementation of polices, there is some variable that can affect the perfomence of the implementation of the policy. Keywords: Implementation Of Policy, Revitalization Area, Old Town Area